2017
DOI: 10.1111/wrr.12514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic insulin treatment on diabetic wound healing

Abstract: This study investigates if different diabetic treatment regimens affects diabetic foot ulcer healing. From January 2013 to December 2014, 107 diabetic foot ulcers in 85 patients were followed until wound healing, amputation or development of a non-healing ulcer at the last follow-up visit. Demographic data, diabetic treatment regimens, presence of peripheral vascular disease, wound characteristics and outcome were collected. Non-healing wound was defined as major or minor amputation or those who didn’t have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 15 publications
2
26
1
2
Order By: Relevance
“…Over a similar timeframe, much lower healing rates have been reported with standard care (eg, 31% at 20 weeks in a meta-analysis30). Even when standard care included insulin, a retrospective cohort study found that only 30% of ulcers had healed after 1.1 month 31. The baseline mean HbA1c was lower in the participants of that study (7.9% or 63 mmol/mol) compared with our own (10.8% or 94 mmol/mol).…”
Section: Discussioncontrasting
confidence: 53%
“…Over a similar timeframe, much lower healing rates have been reported with standard care (eg, 31% at 20 weeks in a meta-analysis30). Even when standard care included insulin, a retrospective cohort study found that only 30% of ulcers had healed after 1.1 month 31. The baseline mean HbA1c was lower in the participants of that study (7.9% or 63 mmol/mol) compared with our own (10.8% or 94 mmol/mol).…”
Section: Discussioncontrasting
confidence: 53%
“…Systemic insulin use has been associated with a higher chance of complete wound healing when adjusted for multiple cofounders. 96,97 There has been growing interest in various vitamins and supplements and their impact on wound healing. In 2017, several RCTs evaluated the use of magnesium, omega-3 fatty acids, zinc sulfate, and vitamin D. [98][99][100][101] All of the aforementioned studies showed significant benefits in reduction in wound size when compared with placebo.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…Obesity is a strong predictor for T2DM ( 155 ). Patients with T2DM exhibit a complex array of complications including a higher prevalence of chronic non-healing wounds, impaired leukocyte function, neuropathy, and vasculopathy ( 156 , 157 ).…”
Section: Diabetes Mellitus Type IImentioning
confidence: 99%
“…Systemic insulin therapy has shown some success in improving wound healing in rats and humans ( 156 , 172 ). Insulin regulates glucose uptake, gene expression, and cell differentiation which all impact skin-resident T cells and wound repair.…”
Section: Diabetes Mellitus Type IImentioning
confidence: 99%
See 1 more Smart Citation